Edukasi Cerdas Menabung : Membangun Kebiasaan Finansial Anak-Anak SDN 168 Desa Sinar Bhakti - Dian Mariska; Devi Puspita; Heni Arinda; Shandra Agustin; Erwanto Erwanto (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The program Smart Saving Education: Building Financial Habits Among Elementary Students of SDN 168 Sinar Bhakti Village was conducted as part of the 34th Community Service Program (KKN) by Universitas Baturaja. This activity aimed to enhance financial literacy among elementary school students from an early age. The main problem identified is the low awareness among children regarding the importance of saving and prudent money management. This program employed an interactive socialization method involving visual aids, educational games, and group discussions to facilitate understanding. The activity was conducted in a one-day session involving 40 students from grades 4, 5, and 6 of SDN 168 Sinar Bhakti. The results indicated improved understanding among students about the importance of saving, as reflected in their ability to explain the benefits of saving, prioritize needs, and create simple plans to save money. Moreover, most students expressed high enthusiasm to start saving independently. The activity also fostered a culture of discussion among students, teachers, and parents regarding basic financial management. These findings indicate that interactive education approaches are effective in fostering good financial habits among children. This program is expected to be a starting point for the sustainable development of financial literacy among younger generations.